2015
DOI: 10.17576/pengurusan-2015-44-14
|View full text |Cite
|
Sign up to set email alerts
|

Kesan Moderator Kearifan Tempatan dalam Mempertingkatkan Prestasi Pekerja di Indonesia

Abstract: ABSTRAK Cabaran kakitangan awam bagi memberikan perkhidmatan yang berkualiti sentiasa diberi keutamaan. Permintaan untuk mendapatkan perkhidmatan yang berkualiti oleh masyarakat awam belum benar-benar tercapai. Ini disebabkan tahap prestasi kerja kakitangan awam masih rendah. Kajian ini bertujuan mengenal pasti tahap prestasi pekerja kakitangan awam. Faktor kompetensi, integriti, disiplin kerja, motivasi kerja, ganjaran dan reka bentuk kerja menjadi elemenelemen dalam mengukur peningkatan prestasi pekerja. Ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…This is because motivation can motivate a person to take the action he or she wants to take (Kotler & Keller, 2016). The findings of this study are in line with other findings of Agus (2006); Suryono (2006); Syafri et al, (2015); Mustapa Kamal et al, (2015); Andjarwati, (2015); Prasetyaningrum (2020); positively and significantly influenced work but all studies did not focus on the performance of the school cooperative business. In line with this, the study focused on the motivational impact of work on school cooperative business performance.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…This is because motivation can motivate a person to take the action he or she wants to take (Kotler & Keller, 2016). The findings of this study are in line with other findings of Agus (2006); Suryono (2006); Syafri et al, (2015); Mustapa Kamal et al, (2015); Andjarwati, (2015); Prasetyaningrum (2020); positively and significantly influenced work but all studies did not focus on the performance of the school cooperative business. In line with this, the study focused on the motivational impact of work on school cooperative business performance.…”
Section: Resultssupporting
confidence: 92%
“…In this study (Dimas, 2011), it was found that the influence of work motivation significantly affected the job satisfaction of individuals. In another study by Agus (2006); Andjarwati (2015); Mustapa Kamal et al (2015); Syafri et al (2015); Prasetyaningrum (2020); Kasino & Indrayanti (2020) has shown that work motivation is a good mediator of positive and significant influence on work.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation